2018
DOI: 10.1175/jpo-d-17-0220.1
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Influence on Baroclinic Instability and the Mesoscale Eddy Field in the Northern North Atlantic Ocean and the Nordic Seas

Abstract: A weak planetary vorticity gradient and weak density stratification in the northern North Atlantic and Nordic seas lead to time-mean currents that are strongly guided by bottom topography. The topographic steering sets up distinct boundary currents with strong property fronts that are prone to both baroclinic and barotropic instability. These instability processes generate a macroturbulent eddy field that spreads buoyancy and other tracers out from the boundary currents and into the deep basins. In this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 49 publications
6
46
0
Order By: Relevance
“…Similar to other parts of the Atlantic (Fratantoni, 2001;McWilliams, 1985), dynamic instability of the mean flows is found to be one of the leading mechanisms of mesoscale eddy generation in the Nordic Seas (Ghaffari et al, 2018;Hattermann et al, 2016;Johannessen et al, 1987;Trodahl & Isachsen, 2018;von Appen et al, 2016). In particular, the above-mentioned eastward increase of the EKE in the Fram Strait goes well with a much higher probability for the development of baroclinic instability along the eastern margin (Trodahl & Isachsen, 2018). At the EGC, the baroclinic instability is inhibited down to the latitude of Jan Mayen.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar to other parts of the Atlantic (Fratantoni, 2001;McWilliams, 1985), dynamic instability of the mean flows is found to be one of the leading mechanisms of mesoscale eddy generation in the Nordic Seas (Ghaffari et al, 2018;Hattermann et al, 2016;Johannessen et al, 1987;Trodahl & Isachsen, 2018;von Appen et al, 2016). In particular, the above-mentioned eastward increase of the EKE in the Fram Strait goes well with a much higher probability for the development of baroclinic instability along the eastern margin (Trodahl & Isachsen, 2018). At the EGC, the baroclinic instability is inhibited down to the latitude of Jan Mayen.…”
Section: Introductionmentioning
confidence: 66%
“…In some studies, barotropic instability is also considered to add to the generation of eddies along the WSC and some sections of the Norwegian Atlantic Slope Current (NwASC) (Ghaffari et al, 2018;Trodahl & Isachsen, 2018). Along the ice edge, where baroclinic and barotropic instability is relatively inefficient (Trodahl & Isachsen, 2018), alternative mechanisms of eddy generation are an interaction of the EGC with rough bottom topography (Johannessen et al, 1987) and an instability of tidal-frequency shelf waves, trapped by the topographic slope (Nilsen et al, 2006). The observed relatively small dominant wavelengths of such waves along the WSC suggest this latter mechanism to generate only relatively small eddies, with radii of 5-10 km.…”
Section: Introductionmentioning
confidence: 99%
“…Both models consist of 35 vertical layers and are stored as daily averages. This temporal resolution is sufficient to resolve the mesoscale and submesoscale processes (Isachsen, ; Trodahl & Isachsen, ). The models also span similar time periods.…”
Section: Methodsmentioning
confidence: 99%
“…Runoff from primary rivers are supplied by monthly climatologies. The 4-km model was validated and analyzed in Trodahl and Isachsen (2018).…”
Section: Eulerian Calculationsmentioning
confidence: 99%
“…Based on the numerical model topography, c 5 0.004 is used for the western basin, where the topographic slope is constant. The choice of c in the eastern basin is not straightforward, as the lower growth rate predicted by the modified Eady theory cannot explain the observed enhanced eddy activity near the steep topographic slope (see discussion in, e.g., Trodahl and Isachsen 2018). Here, we follow the study of Bracco et al (2008) who suggested that a very steep topographic slope can be seen as a vertical wall.…”
Section: B a Conceptual Model With One Basin And A Single Boundary Cmentioning
confidence: 96%